Case report: A rare case of neurocytoma of the Vth cranial nerve - Gui, Yongping; Zhou, Fanghua; Li, Bin; Wu, Bin; Huang, Xingen (Frontiers in Oncology, 2024)
We report a case of neurocytoma originating from cranial nerve V. A 53-year-old female patient presented with a 20-day history of right frontotemporal facial paresthesia and pain. Magnetic resonance imaging (MRI) showed a 2.5-cm × 1.4-cm “dumbbell” enhancing lesion located in the cisternal segment of cranial nerve V with extension into Meckel’s cave, and the signal characteristics were suggestive of trigeminal neurinoma. The lesion was resected through a subtemporal middle cranial fossa approach. Intraoperative findings revealed that the tumor originated from the cisternal segment of cranial nerve V and extended into Meckel’s cave through the trigeminal foramen. No dural attachment was found. The tumor was debulked using sharp dissection and bipolar cautery under the microscope. Extraventricular neurocytomas (EVNs) are extremely rare tumors of the central nervous system. To date, only two cases of neurocytomas arising from cranial nerve VIII have been described. This paper summarizes the clinicopathological features of a case of neurocytoma originating from the cisternal segment of cranial nerve V with extension into Meckel’s cave and expounds the relevant diagnoses and treatments, which may provide a practical clinical basis and experience for the diagnosis and treatment of EVN in the future.